2009
DOI: 10.3156/jsoft.21.194
|View full text |Cite
|
Sign up to set email alerts
|

A System for Affect Analysis of Utterances in Japanese Supported with Web Mining

Abstract: We propose a method for affect analysis of textual input in Japanese supported with Web mining. The method is based on a pragmatic reasoning that emotional states of a speaker are conveyed by emotional expressions used in emotive utterances. It means that if an emotive expression is used in a sentence in a context described as emotive, the emotion conveyed in the text is revealed by the used emotive expression. The system ML-Ask (Emotive Elements / Expressions Analysis System) is constructed on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Ptaszynski et al (2009a) already showed that ML-Ask and Shi's technique are compatible and can be used as complementary means to improve the emotion recognition task. However, these two methods are based on different assumptions.…”
Section: Web Mining Technique For Emotion Association Extractionmentioning
confidence: 97%
“…Ptaszynski et al (2009a) already showed that ML-Ask and Shi's technique are compatible and can be used as complementary means to improve the emotion recognition task. However, these two methods are based on different assumptions.…”
Section: Web Mining Technique For Emotion Association Extractionmentioning
confidence: 97%
“…Evaluations ML-Ask has been evaluated a number of times on different datasets and frameworks. In first evaluations, Ptaszynski et al [12,20,21] focused on evaluating the system on separate sentences. For example, in [20], there were 90 sentences (45 emotive and 45 non-emotive) annotated by authors of the sentences (first-person standpoint annotations).…”
Section: Quality Controlmentioning
confidence: 99%
“…On this dataset ML-Ask achieved 83% of balanced F-score for determining whether a sentence is emotive, 63% of human level of unanimity score for determining emotive value and 45% of balanced F-score for detecting particular emotion types. In [12] Ptaszynski et al added annotations of third-party annotators and performed additional evaluation from the third-person standpoint. The evaluation showed that ML-Ask achieves better performance when supported by additional Web-mining procedure (not included in the OpenSource version) for extracting emotive associations from the Internet.…”
Section: Quality Controlmentioning
confidence: 99%
“…Furthermore, although it was proved that affective states should be analysed as emotion specific (Lerner & Kelter, 2000), most of the behavioural approach methods simply classify them to opposing pairs such as joy-anger, or happiness-sadness (Teixeira et al, 2008). A positive change in this tendency can be seen in text mining and information extraction approaches to emotion estimation (Tokuhisa et al, 2008;Ptaszynski et al, 2009b). However, the lack of standardization often causes inconsistencies in emotion classification.…”
Section: Implementing Emotional Intelligence In Conversational Agentsmentioning
confidence: 99%
“…However, the lack of standardization often causes inconsistencies in emotion classification. As one of the recent advances in affect analysis, it was shown that Web mining methods can improve the performance of language-based affect analysis systems (Tokuhisa et al, 2008;Ptaszynski et al, 2009b). However, in such methods, although the results of experiments appear to be positive, the two different approaches, the language-syntax based and Web mining based, are mixed.…”
Section: Implementing Emotional Intelligence In Conversational Agentsmentioning
confidence: 99%